The Influence of Social Media Public Relations on the Media Image of "Women’s Talk" Among Generation Z - Sri Narti; Ali Salman; Maryaningsih; Aditya Febrian Surya Baskara; Elsabila Larasati (Journal Transnational Universal Studies, 2026)
This study was motivated by the growing role of social media as a digital public relations space in shaping public perceptions of media organizations. Women’s Talk, as a digital media platform addressing women’s issues, lifestyle, and education, requires communication management that is informative, interactive, consistent, creative, and capable of engaging young audiences. This study aimed to analyze the influence of social media public relations on the image of Women’s Talk among Generation Z. The research employed an explanatory quantitative approach using a questionnaire-based survey with a 5-point Likert scale. The study population consisted of 80 students from the 2023 cohort of the Communication Science Study Program in classes A1, A2, and A3, with a sample of 49 respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results showed that all indicators had outer loadings above 0.70, Cronbach’s alpha values above 0.90, composite reliability values above 0.90, and average variance extracted (AVE) values above 0.50, indicating that the measurement model met the required validity and reliability criteria. The hypothesis test produced a path coefficient of 0.672, a t-statistic of 7.018, and a p-value of